Perforated diode neutron sensors - McNeil, Walter J. (Kansas State University, 2010)
A novel design of neutron sensor was investigated and developed. The perforated, or micro-structured, diode neutron sensor is a concept that has the potential to enhance neutron sensitivity of a common solid-state sensor configuration. The common thin-film coated diode neutron sensor is the only semiconductor-based neutron sensor that has proven feasible for commercial use. However, the thin-film coating restricts neutron counting efficiency and severely limits the usefulness of the sensor. This research has shown that the perforated design, when properly implemented, can increase the neutron counting efficiency by greater than a factor of 4. Methods developed in this work enable detectors to be fabricated to meet needs such as miniaturization, portability, ruggedness, and adaptability. The new detectors may be used for unique applications such as neutron imaging or the search for special nuclear materials. The research and developments described in the work include the successful fabrication of variant perforated diode neutron detector designs, general explanations of fundamental radiation detector design (with added focus on neutron detection and compactness), as well as descriptive theory and sensor design modeling useful in predicting performance of these unique solid-state radiation sensors. Several aspects in design, fabrication, and operational performance have been considered and tested including neutron counting efficiency, gamma-ray response, perforation shapes and depths, and silicon processing variations. Finally, the successfully proven technology was applied to a 1-dimensional neutron sensor array system.
Keywords: neutron sensor; neutron detector; Engineering, Nuclear (0552); Physics, Radiation (0756)